The Education of Ulama Cadres in Muhammadiyah Islamic Boarding School Karangasem Paciran Lamongan, Indonesia - Ibnu Habibi; Tobroni Tobroni; Triyo Supriyatno; Ahmad Barizi (Universitas Muhammadiyah Malang, 2024)
This research analyses the education of ulama cadres at the Muhammadiyah Islamic Boarding School, Karangasem Paciran Lamongan. This research uses a qualitative descriptive method with a case study approach. The techniques used in collecting data were observation, interviews, and documentation. Checking the validity of the data by triangulating sources and methods. Meanwhile, data analysis includes condensation, presentation, verification, and conclusion. The results of the research concluded: First, the concept of Ulama in Muhammadiyah Islamic boarding schools is to have professional competence, personal competence, social competence, and spiritual competence. Second, the strategy used by Islamic boarding schools to carry out education for ulama cadres is (a) education and training carried out in formal education and Islamic madrasas; (b) encouragement to memorize the Qur'an; (c) familiarization with students' activities; (d) field practice for preaching in the community. There are two variants in the education of ulama cadres, namely genetic and social theory (3). The educational implications of Muhammadiyah Islamic boarding school ulama cadres are (a) the existence of beneficial community service activities through da'wah weeks and field da'wah service; (b) there is an increase in the Islamic boarding school's clerical competence; (c) there is high satisfaction and trust in the community towards graduates of the two Islamic boarding schools, making it easier for graduates to play an active role in empowering the community, especially in the religious sector.